Analisis Indeks Kepuasan Kepuasan Masyarakat terhadap Pelayanan Administrasi Kependudukan pada Dinas Kependudukan dan Pencatatan Sipil Kota Bukittinggi - Gita Oktaviani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Public services in the field of population administration play a crucial role in fulfilling citizens’ rights and improving government performance. This study aims to analyze the Community Satisfaction Index (CSI) regarding the quality of services provided by the Department of Population and Civil Registration of Bukittinggi City. The research employed a quantitative descriptive method with survey techniques using questionnaires distributed to service users. Data were processed by calculating the satisfaction index based on predetermined indicators. The findings indicate that the overall level of community satisfaction falls into the “good” category, although some service aspects such as waiting time and service clarity still require improvement. These results provide valuable input for the agency in formulating strategies to enhance service quality and strengthen public trust.